Structural and Kinetic Basis of Steroid 17α,20-Lyase Activity in Teleost Fish Cytochrome P450 17A1 and Its Absence in Cytochrome P450 17A2 - Pallan, Pradeep S.; Nagy, Leslie D.; Lei, Li; Gonzalez, Eric; Kramlinger, Valerie M.; Azumaya, Caleigh M.; Wawrzak, Zdzislaw; Waterman, Michael R.; Guengerich, F. Peter; Egli, Martin (The Journal of biological chemistry, 2015)
Cytochrome P450 (P450) 17A enzymes play a critical role in the oxidation of the steroids progesterone (Prog) and pregnenolone (Preg) to glucocorticoids and androgens. In mammals, a single enzyme, P450 17A1, catalyzes both 17α-hydroxylation and a subsequent 17α,20-lyase reaction with both Prog and Preg. Teleost fish contain two 17A P450s; zebrafish P450 17A1 catalyzes both 17α-hydroxylation and lyase reactions with Prog and Preg, and P450 17A2 is more efficient in pregnenolone 17α-hydroxylation but does not catalyze the lyase reaction, even in the presence of cytochrome b5. P450 17A2 binds all substrates and products, although more loosely than P450 17A1. Pulse-chase and kinetic spectral experiments and modeling established that the two-step P450 17A1 Prog oxidation is more distributive than the Preg reaction, i.e. 17α-OH product dissociates more prior to the lyase step. The drug orteronel selectively blocked the lyase reaction of P450 17A1 but only in the case of Prog. X-ray crystal structures of zebrafish P450 17A1 and 17A2 were obtained with the ligand abiraterone and with Prog for P450 17A2. Comparison of the two fish P450 17A-abiraterone structures with human P450 17A1 (DeVore, N. M., and Scott, E. E. (2013) Nature 482, 116–119) showed only a few differences near the active site, despite only ∼50% identity among the three proteins. The P450 17A2 structure differed in four residues near the heme periphery. These residues may allow the proposed alternative ferric peroxide mechanism for the lyase reaction, or residues removed from the active site may allow conformations that lead to the lyase activity. Background: Fish (and human) P450 17A1 catalyze both steroid 17α-hydroxylation and 17α,20-lyase reactions. A second fish P450, 17A2 (51% identical), catalyzes only 17α-hydroxylation. Results: Crystal structures of zebrafish P450 17A1 and 17A2 and human P450 17A1 are very similar. Conclusion: In kinetic analysis, the two-step oxidation of progesterone is more distributive than for pregnenolone. Significance: Small structural differences are associated with activities of the two fish P450s.